Psychology and theology of submission: understanding Islamic religiosity and spirituality - Abdullah, Fatimah (2013)
Religiosity and spirituality are inseparable.Religiosity in Islam characterized by true submission which can only be built on the connerstone of knowledge about the nature of God and that of man.